A Study On Exploring Fundamental Aspects Of Corporate Governance In Family Enterprises: Evidence From India. (International Journal of Environmental Sciences, 2025)
This study aims to explore and analyze the fundamental aspects of corporate governance in family-owned businesses by comparing them with non-family-owned firms listed on the National Stock Exchange (NSE) of India. Drawing on secondary data collected from 200 companies—comprising 100 family-owned and 100 non-family-owned firms—this research investigates key governance variables such as ownership concentration, board composition, independence, succession planning, gender diversity, and transparency, alongside financial performance indicators like Return on Assets (ROA), Return on Equity (ROE), and market capitalization. The study adopts a descriptive and comparative research design, using statistical tools including t-tests, ANOVA, chi-square tests, and correlation analysis to assess the structural and performance-related governance disparities between the two firm types. Findings reveal that family-owned firms are characterized by higher promoter shareholding, limited board independence, lower gender diversity, informal succession processes, and weaker ESG disclosure practices compared to their non-family counterparts. However, governance maturity appears to improve across generations in family firms, with third-generation businesses displaying relatively stronger formalization and governance indicators. The study also identifies a positive correlation between governance quality and financial performance, reinforcing the strategic importance of adopting transparent and structured governance mechanisms. In contrast to stewardship theory's optimistic view of family leadership, the results suggest that without formal governance practices, family control may hinder accountability and performance. The paper contributes to the literature by offering empirical evidence from the Indian context and emphasizing the need for regulatory and institutional interventions to enhance governance in family enterprises. Limitations include the exclusive use of secondary data and a cross-sectional design, which future research could address through longitudinal and qualitative methods. Overall, this study highlights the duality of tradition and transformation in family business governance and offers actionable insights for practitioners, policymakers, and scholars alike.